Diagnostic performance of anti‐cyclic citrullinated peptide and rheumatoid factor in patients with rheumatoid arthritis. (4th May 2015) - Chang, Pi‐Yueh; Yang, Cheng‐Tao; Cheng, Ching‐Hui; Yu, Kuang‐Hui
Abstract: Aim: To compare the diagnostic performance of rheumatoid factor (RF) and anti‐cyclic citrullinated peptide antibody (anti‐CCP) in the diagnosis of patients with rheumatoid arthritis (RA) in Taiwan. Methods: Serum concentrations of RF and anti‐CCP were measured in 246 cases, including 39 patients with RA and 207 patients with other rheumatic diseases (non‐RA). The age, sex, clinical presentation, RF, anti‐CCP results and the final diagnoses were recorded and analyzed. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+) and negative likelihood ratio (LR−) were calculated. Results: Among all 246 patients, 39 (15.9%) were diagnosed with RA and 207 (84.1%) were diagnosed with other rheumatic diseases (non‐RA). In the diagnosis of RA, the sensitivity, specificity, PPV, NPV, LR+ and LR− of the RF test were 67%, 79%, 37%, 93%, 3.12, and 0.42, respectively. The corresponding data for the anti‐CCP test were 79%, 98%, 86%, 96%, 32.91 and 0.21, respectively. The presence of either anti‐CCP or RF increased the sensitivity to 85%, and when they both were present, the specificity increased to 98%. Among the 39 RA patients, 26 (66.7%) tested positive for RF, and 31 (79.5%) tested positive for anti‐CCP. RF was positive in two of eight anti‐CCP‐negative patients with RA, and anti‐CCP was positive in seven of 13 RF‐negative patients with RA. Conclusions: The RF and anti‐CCP tests are complementary, and the co‐detection of these antibodies can increase the detection rate and provide important clinical value in the diagnosis of RA. Both anti‐CCP and RF positivity are useful for the diagnosis of RA, and use of both tests together improves the diagnostic sensitivity.